Subterranean Survivorship and Seasonal Emergence of Laricobius spp. (Coleoptera: Derodontidae), Biological Control Agents for the Hemlock Woolly Adelgid. Issue 1 (22nd November 2021) - Foley, Jeremiah R; McAvoy, Thomas J; Grubb, Christopher; Mayfield, Albert E; Strahm, Brian; Salom, Scott M
Abstract: Following the adventive arrival, subsequent spread, and ensuing impact of Adelges tsugae Annand (Hemiptera: Adelgidae), the hemlock woolly adelgid (HWA) in the eastern United States, a robust initiative was launched with the goal of decreasing ecosystem impacts from the loss of eastern hemlock (Pinales: Pinaceae). This initiative includes the use of biological control agents, including Laricobius spp. (Insecta: Coleoptera). Laboratory production of these agents is limited by subterranean mortality and early emergence. Therefore, the subterranean survivorship and timing of emergence of a mixture of Laricobius spp. was investigated. PVC traps internally lined with a sticky card and covered with a mesh screen were inserted into the soil to measure the percent emergence of adults based on the number of larvae placed within. The number of emerged adults in the field and laboratory-reared larval treatments was adjusted based on emergence numbers in the control and used as the response variable. Independent variables included in the final model were: treatment (field-collected vs. laboratory-reared), organic layer depth (cm), soil pH, and April-to-December mean soil moisture. No differences were found in survivorship between field-collected and laboratory-reared treatments. As pH and organic layer increased survivorship decreased, significantly. Although the majority of emergence occurred in the fall, emergence also occurred in spring and summer. The occurrence of spring and summer emergence and low survivorship (17.1 ± 0.4%) in the field across all treatments suggests that these are characteristics of Laricobius spp. field biology in their introduced range and not artifacts of the laboratory rearing process.